ASSESSMENT OF THE HYPOLIPIDEMIC EFFECT OF ANTIHYPERTENSIVE THERAPY IN PATIENTS WITH A COMBINATION OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE AND ARTERIAL HYPERTENSION - Farajova, N.A.; Rahimova, T.N.; Sultanova, S.S.; Ismayilova, N.R.; Huseynova, N.N. (World of Medicine and Biology, 2026)
The urgency of the problem of chronic obstructive pulmonary disease, in addition to the increase in morbidity and mortality, is also due to comorbidity, in particular with arterial hypertension, which increases the risk of cardiovascular events. The state of lipid metabolism is of particular importance in this context. The aim of the study was to study the dynamics of lipid metabolism according to the results of antihypertensive therapy in patients with a combination of chronic obstructive pulmonary disease and arterial hypertension. 58 patients with chronic obstructive pulmonary disease and arterial hypertension were examined without gender differences. Arterial hypertension was recorded at blood pressure ≥140/90 mmHg. All patients had grade 2 hypertension. A triple combination of perindopril, indapamide and amlodipine, was prescribed as an antihypertensive drug in doses of 10+2.5+10 and 5+1.25+5 mg. Statins were not included in the treatment regimen for both obstructive pulmonary disease and arterial hypertension. Systolic and dystolic blood pressure, total cholesterol, triglycerides, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and very low-density lipoprotein cholesterol were determined. The results of the study showed the high effectiveness of antihypertensive therapy, regardless of the category of patients, as well as its pleiotropic effect in the form of positive dynamics of the atherogenic blood lipid fraction.
Keywords: chronic obstructive pulmonary disease; hypertension; antihypertensive therapy; lipid metabolism; patients of category B; patients of category E